Association of vitamin A and D deficiency and the presence of sepsis in the geriatric population: a cross-sectional study - Feng, Yichuan; Xuan, Pengfei; Kang, Ping; Yang, Jingping; Wang, Hongyan; Li, Tiewei (Frontiers in Nutrition, 2025)
BackgroundExtensive research has established that vitamins A (VA) and D (VD) are essential to immune function. Deficiencies in these vitamins are associated with increased susceptibility to infections and more severe disease outcomes. However, the relationship between VA and VD deficiency and sepsis in geriatric persons (aged > 60 years) remains underexplored. The aim of this study was to investigate the association between sepsis incidence in persons over 60 and deficiencies in VA and VD.Methods39 geriatric patients diagnosed with sepsis between August 2024 and April 2025 were consecutively enrolled. Among the sepsis patients, 15 succumbed during hospitalization. During the same period, 28 geriatric patients hospitalized with common infectious diseases were recruited as controls. Online medical files at the time of hospitalization were used to gather medical and laboratory information retrospectively. Everyone who participated had their peripheral blood samples taken, and ultra-performance liquid chromatography tandem mass spectrometry helped us assess serum concentrations of 25-hydroxyvitamin D3 [25(OH)D3], 25-hydroxyvitamin D2 [25(OH)D2], and retinol (VA). The combined concentration of 25(OH)D3 and 25(OH)D2 helped calculate the overall VD levels. SPSS 24.0 (IBM Corp., Armonk, NY, USA) helped carry out all analyses.ResultsIn comparison to controls, geriatric patients with sepsis demonstrated significantly lower serum VA and VD levels, alongside a notably higher deficiency rate for both vitamins. Correlation analyses revealed significant inverse associations between serum levels of VA and VD and the infection marker procalcitonin (PCT) as well as the inflammatory marker interleukin-6 (IL-6). Multivariate regression analysis showed that in persons over 60, deficiencies in either VA or VD were independently associated with significantly higher odds of sepsis.ConclusionVitamins A and VD deficiencies were associated with lower serum levels in geriatric sepsis patients and were inversely correlated with PCT and IL-6. Furthermore, deficiencies in either vitamin were independently associated with a higher prevalence of sepsis in this population.